The curative effect of liposuction curettage in the treatment of bromhidrosis: A meta-analysis. Issue 33 (August 2017) - Zhang, Lianbo; Chen, Feifei; Kong, Jiao; Li, Zhuonan; Wen, Xiaoqiang; Liu, Jun
Abstract: Background: We aimed to understand the curative effect of liposuction curettage (LC) in the treatment of bromhidrosis. Methods: Relevant studies published before January 2017were searched from the PubMed, Embase, Cochrane Library, Wanfang, VIP, and China National Knowledge Infrastructure databases. Parameters including recurrence, complications, complete response, and overall response were assessed. Meta-analysis was performed using the R 3.12 statistical package. Odds ratio (OR) and 95% confidence interval (95% CI) were used for dichotomous data. Heterogeneity was assessed using Cochran's Q-statistic and I 2 test. In addition, Egger's test was conducted to detect publication bias. Results: Ten studies with a total of 1124 participants (545 cases and 579 controls) were included. There was no statistical difference in recurrence (OR = 1.19, 95% CI: 0.51–2.74), complete response (OR = 0.66, 95% CI: 0.25–1.74), or overall response (OR = 0.63, 95% CI: 0.21–1.87) between the case and control groups. The incidence of complications in the case group was lower than that in the control group (OR = 0.24, 95% CI: 0.08–0.67) and open excision group (OR = 0.11, 95% CI: 0.07–0.19). Publication bias existed for the recurrence index in the open excision group ( t  = 3.3979, P  = .04), but no publication bias was found in other subgroups, indicating stable results. Conclusions: LC, which has fewer complications, can be considered the primary choice in the treatment of patients with bromhidrosis compared with other surgical procedures.